The world economy - Siebert, Horst (London ; New York : Routledge, 2002)
The tendency of most textbooks in international economics is to look at the world economy from the point of view of one country. The second edition of Horst Siebert's The World Economy rebels against this tendency and treats the world as a single entity. The key issues that have affected the world trade system since the turn of the millennium are thus very much to the fore
Includes bibliographical references (p. 301-308) and index.
oif 08/08/16
Loan
Keywords: Economic history; Finance; Economic development; Competition, International